ChemInform Abstract: Gold(I)‐Catalyzed Tandem Transformation with Diynes: Rapid Access to Linear Cyclopentenone‐Fused Polycyclic Molecules. Issue 4 (January 2016) - Yu, Congjun; Chen, Bin; Zhou, Tian; Tian, Qingshan; Zhang, Guozhu
Abstract: Conditions A) allow a rapid access to a broad spectrum of title ring systems where a wide variety of functionalities is tolerated.